2015
DOI: 10.1002/humu.22736
|View full text |Cite
|
Sign up to set email alerts
|

Genome Annotation by Shotgun Inactivation of a Native Gene in Hemizygous Cells: Application toBRCA2with Implication of Hypomorphic Variants

Abstract: The greatest interpretive challenge of modern medicine may be to functionally annotate the vast variation of human genomes. Demonstrating a proposed approach, we created a library of BRCA2 exon 27 shotgun-mutant plasmids including solitary and multiplex mutations to generate human knockin clones using homologous recombination. This 55-mutation, 13-clone syngeneic variance library (SyVaL) comprised severely affected clones having early-stop nonsense mutations, functionally hypomorphic clones having multiple mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(56 reference statements)
1
0
0
Order By: Relevance
“…As previously published, both FANCC - and BRCA2 -deficient cells were more sensitive to MMC treatment ( Supplementary Fig. S2B and Supplementary Table S6 ) 32 44 45 . Surprisingly, we observed that BRCA2 (+/−), BRCA2 (−/−) and FANCC (−/−) clones were more sensitive to MK-1775 than parental clones ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 81%
“…As previously published, both FANCC - and BRCA2 -deficient cells were more sensitive to MMC treatment ( Supplementary Fig. S2B and Supplementary Table S6 ) 32 44 45 . Surprisingly, we observed that BRCA2 (+/−), BRCA2 (−/−) and FANCC (−/−) clones were more sensitive to MK-1775 than parental clones ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 81%